Berczeli Anzelm Károlyhoz - Babits boríték (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1935)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek